2004
DOI: 10.1111/j.1365-2044.2004.03837.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propofol and isoflurane anaesthesia on the immune response to surgery*

Abstract: SummaryThere are two major subpopulations of peripheral helper T lymphocytes: T helper 1 (Th1) and T helper 2 (Th2) cells. Surgical stress increases the number of Th2 cells, and decreases that of Th1 cells, resulting in a decrease in the Th1 ⁄ Th2 ratio, and, consequently, in suppressed cellmediated immunity. Since anaesthesia can suppress the stress response to surgery, it may inhibit the decrease in the Th1 ⁄ Th2 ratio. Using flow cytometry, we studied whether propofol anaesthesia (n = 9) or isoflurane anaes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 27 publications
6
102
0
7
Order By: Relevance
“…The Anti-Inflammatory and Immunosuppressive Properties of Inhaled Anaesthetics -Data from Experimental Studies and Clinical Implications remained unchanged after the use of propofol (47).…”
Section: The Impact Of Volatile Anaesthetics On the Function Of Lymphmentioning
confidence: 90%
“…The Anti-Inflammatory and Immunosuppressive Properties of Inhaled Anaesthetics -Data from Experimental Studies and Clinical Implications remained unchanged after the use of propofol (47).…”
Section: The Impact Of Volatile Anaesthetics On the Function Of Lymphmentioning
confidence: 90%
“…Aucune réduction significative du rapport Th1/Th2 n'a été observée quand le propofol était utilisé pour l'entretien de l'anesthésie chez les patients subissant une craniotomie. 18 Il a été également montré que le propofol le supprime la production de PGE2 par les monocytes via un effet sur l'activité de la cyclo-oxygénase.…”
Section: Propofolunclassified
“…Human studies showed a significant reduction in Th1:Th2 ratio when isoflurane was compared with propofol. 18 In vitro experiments revealed DNA damage to human peripheral blood lymphocytes in a dose-dependent manner following exposure to halothane, isoflurane, sevoflurane, and desflurane. Volatile anesthetics are known to upregulate expression of hypoxia-inducible factors, which are important for maintaining normal cellular function in hypoxic conditions but which are also associated with tumorigenesis and poor cancer prognosis.…”
Section: Inhalational Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio was significantly lower with isoflurane than propofol. Propofol anaesthesia attenuated the surgical stress-induced adverse immune response better than isoflurane anaesthesia [5].…”
Section: Introductionmentioning
confidence: 99%